Choreographing discourses a Mark Franko reader - Franko, Mark (Abingdon, Oxon New York, NY Routledge, 2019)
"Choreographing Discourses brings together essays originally published by Mark Franko between 1996 and the contemporary moment. Assembling these essays from international, sometimes un-translated sources, and curating their relationship to a rapidly-changing field, this Reader offers an important resource in the dynamic scholarly fields of dance and performance studies. What makes this volume especially appropriate for undergraduate and graduate teaching is its critical focus on twentieth and twenty-first-century dance artists and choreographers. Among these Oskar Schlemmer, Merce Cunningham, Kazuo Ohno, William Forsythe, Bill T. Jones, and Pina Bausch, some of the most high-profile European, American, and Japanese artists of the past century. The volume's constellation of topics delves into controversies that are essential turning points in the field (notably Still/Here and Paris is Burning), which illuminate the spine of the field while interlinking dance scholarship with performance theory, film, visual, and public art. The volume contains the first critical assessments of Franko's contribution to the field by André Lepecki and Gay Morris, and an interview incorporating a biographical dimension to the development of Franko's work and its relation to his dance and choreography. Ultimately, this Reader encourages a wide scope of conversation and engagement, opening up core questions in ethics, embodiment, and performativity"-- Provided by publisher
Foreword / Randy Martin -- Preface / Mark Franko -- Introduction. Reconceptualizing time, historical time, and the time of interpretation / Gay Morris -- Theory's moves / André Lepecki -- Writing for the body : notation, reconstruction, and reinvention in dance -- History/theory : criticism/practice -- From Croce's critical condition to the choreographic public sphere -- Splintered encounters : the critical reception of William Forsythe in the US, 1979-1989 -- Archeological choreographic practices : Foucault and Forsythe -- Figurae : re-translating the encounter between Peter Welz, William Forsythe, and Francis Bacon -- Dance and figurability -- Can we inhabit a dance? : reflections on dancing the "Bauhaus dances" in Dessau -- The ready-made as movement : Cunningham, Duchamp, and Nam June Paik's two Merces -- Dance as sign and unruly corporeality in Pasolini's film and theory -- The dancing gaze across cultures : Kazuo Ohno's Admiring la Argentina -- Bausch and the symptom -- The quarrel of the queen and the transvestite : sexuality, class, and subculture in Paris is burning -- Dance, the de-materialization of labor, and the productivity of the corporeal -- In the company of Donya Feuer : an interdisciplinary method -- In conversation : Alessandra Nicifero with Mark Franko
Includes bibliographical references and index
Keywords: Choreography; Dance